Welcome to the neighborhood : an anthology of American coexistence - Green, Sarah Elizabeth, 1980-; Baker, David, 1954- (Swallow Press, 2019)
"How to live with difference--not necessarily in peace, but with resilience, engagement, and a lack of vitriol--is a defining worry in America at this moment. The poets, fiction writers, and essayists (plus one graphic novelist) who contributed to Welcome to the Neighborhood don't necessarily offer roadmaps to harmonious neighboring. Some of their narrators don't even want to be neighbors. Maybe they grieve, or rage. Maybe they briefly find resolution or community. But they do approach the question of what it means to be neighbors, and how we should do it, with open minds and nuance. The many diverse contributors give this collection a depth beyond easy answers. Their attentions to the theme of neighborliness as an ongoing evolution offer hope to readers: possible pathways for rediscovering community, even just by way of a shared wish for it. The result is an enormously rich resource for the classroom and for anyone interested in reflecting on what it means to be American today, and how place and community play a part."--